Depression of Tissue-Type Plasminogen Activator and Enhancement of Urokinase-Type Plasminogen Activator as an Expression of Local Inflammation - Brommer, Emile J P; Dooijewaard, Gerard; Dijkmans, Ben A C; Breedveld, Ferdinand C (Thrombosis and Haemostasis, 1992)
Inflammatory processes are accompanied by extravascular deposition and breakdown of fibrin. We measured fibrinolytic parameters in synovial fluid (SF) and in plasma of 36 patients with rheumatoid arthritis (RA). As a control, SF of 13 patients with blunt knee trauma, and plasma of 17 healthy volunteers were studied. In RA patients, extravascular t-PA mediated plasminogen activation was depressed: mean SF tissue-type plasminogen activator (t-PA:Ag) concentration (2.1 ± 1.6 ng/ml) was four-fold lower, and plasminogen activator inhibitor (PAI) activity (284 ± 212%) four-fold higher than the plasma values of the same patients or of healthy donors. In contrast, u-PA related plasminogen activation was strongly enhanced: urokinase-type plasminogen activator (u-PA) antigen (23.1 ±12.4 ng/ml) was more than four-fold higher, single-chain u-PA (scu-PA) (5.3 ± 1.9 ng/ml) three-fold higher than in plasma of the same patients or of healthy donors, and active two-chain u-PA (tcu-PA) was detected in 14 of the 36 SF samples of RA patients. All of these changes in extravascular fibrinolytic parameters correspond with those induced by inflammatory mediators in cell cultures. In joint effusions of patients with a blunt knee trauma, the effects were intermediate: u-PA related parameters showed moderate changes in the same direction as in arthritis; t-PA antigen was also decreased. The only exception was that PAI was not increased. We conclude that the findings in traumatic effusions reflect transient effects as a reaction to trauma. In joint inflammation, the depressed t-PA mediated plasminogen activation, although more than compensated by the enhanced u-PA mediated plasminogen activation, results in protraction of fibrin removal. Besides, the enhanced u-PA activation might lead to proteolytic damage of the cartilage.